PENGARUH PENEMPATAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT.PEGADAIAN (Persero) AREA PADANG - Hendar Kushendarto; Erni Masdupi (Jurnal Riset Manajemen Bisnis dan Publik, 2015)
This research was intended to express : 1. The influence of Placement towards  motivation on PT. Pegadaian (Persero) Area Padang, 2. The influence of placement and Job environment towards motivation on PT. Pegadaian (Persero) Area Padang, 3. The influence of Placement, Job environment and motivation towards job satisfaction on PT. Pegadaian (Persero) Area Padang. The size of population as much as 100 peoples. The technique of samples Proportional Random Sampling. The samples of this research are the employees of PT. Pegadaian (Persero) Area Padang as much as 80 employees. The data collected through a questionnaire using scale models Likert that has been examined the vaidity and the reliability. The technique of analysis data are used Path Analysis with the help of SPSS (statistical package for social science) program. The results of this research are : 1. There is a significant influence between Placement towards  motivation for the Employee on PT. Pegadaian (Persero) Area Padang, 2. There is a significant influence between Placement, Job environment towards motivation and, 3. There is a significant influence between placement, Job environment dan  motivation towards job satisfaction on PT. Pegadaian (Persero) Area  padang. Judging from the  influence of direct and indirect Placement, Job environment and  motivation towards job satisfaction on PT. Pegadaian (Persero)  Padang as much as 47,52 % obtained that motivation have the greatest influence as much as 15,76 %.